1998
DOI: 10.1029/98ja02662
|View full text |Cite
|
Sign up to set email alerts
|

Polar wind survey with the Thermal Ion Dynamics Experiment/Plasma Source Instrument suite aboard POLAR

Abstract: Abstract. In February 1996, the POLAR spacecraft was placed in an elliptical orbit with a 9 RE geocentric distance apogee in the northern hemisphere and 1.8 RE perigee in the southern hemisphere. The Thermal Ion Dynamics Experiment (TIDE) on POLAR has allowed sampling of the three-dimensional ion distribution functions with excellent energy, angular, and mass resolution. The Plasma Source Instrument (PSI), when operated, allows sufficient diminution of the electric potential to observe the polar wind at very h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
195
5

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(221 citation statements)
references
References 65 publications
21
195
5
Order By: Relevance
“…However, our method is much more sensitive to lighter ion species, since their lower energy will make them more affected by the spacecraft potential and thus create a larger wake. Moreover, hydrogen is the dominant ion species in the low-energy high-latitude ion outflows (Su et al, 1998). Our calculated velocity can thus be regarded as the proton velocity, and later comparison of the properties of the outflowing ions to previous measurements will therefore only regard the hydrogen component of the flow.…”
Section: Methods Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our method is much more sensitive to lighter ion species, since their lower energy will make them more affected by the spacecraft potential and thus create a larger wake. Moreover, hydrogen is the dominant ion species in the low-energy high-latitude ion outflows (Su et al, 1998). Our calculated velocity can thus be regarded as the proton velocity, and later comparison of the properties of the outflowing ions to previous measurements will therefore only regard the hydrogen component of the flow.…”
Section: Methods Limitationsmentioning
confidence: 99%
“…The current understanding of the high-latitude ion outflows, including the polar wind, can mainly be attributed to a wealth of studies from Akebono (Abe et al, 1993(Abe et al, , 1996(Abe et al, , 2004Cully et al, 2003a) and Polar (e.g. Moore et al, 1997;Su et al, 1998;Chappell et al, 2000;Lennartsson et al, 2004;Liemohn et al, 2005;Huddleston et al, 2005;Peterson et al, 2006). More details on the previous measurements of the high-latitude ion outflows can be found in the recent review articles by Yau et al (2007) and Moore and Horwitz (2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This has been evidenced by many observational studies and models (Abe et al, 1993;Su et al, 1998a, b;Glocer et al, 2012;Maes et al, 2015). Maes et al (2015), studying outflow above smallscale polar cap arcs using Cluster (Escoubet et al, 2001) measurements, found that the upflow above the polar cap can be roughly divided into two distinct groups based on the solar zenith angle (SZA) of the footpoint of the field line in the ionosphere.…”
Section: Introductionmentioning
confidence: 99%
“…The low energization also means that it is very difficult for O + ions to escape Earth's gravitational potential via this mechanism, and so very little O + is expected in the polar wind. Nevertheless, O + ions have been observed above the polar caps and in the lobes (Nagai et al, 1984;Waite Jr. et al, 1985;Abe et al, 1993;Su et al, 1998a). Many additional mechanisms have been proposed to explain this (see, e.g., Tam et al, 2007, for an overview).…”
Section: Introductionmentioning
confidence: 99%